A Study of Graphene‐Based Copper Catalysts: Copper(I) Nanoplatelets for Batch and Continuous‐Flow Applications. Issue 17 (13th August 2019) - De Angelis, Sonia; Franco, Mario; Triminì, Alessandra; González, Ana; Sainz, Raquel; Degennaro, Leonardo; Romanazzi, Giuseppe; Carlucci, Claudia; Petrelli, Valentina; de la Esperanza, Alejandro; Goñi, Asier; Ferritto, Rafael; et al.
Abstract: The use of graphene derivatives as supports improves the properties of heterogeneous catalysts, with graphene oxide (GO) being the most frequently employed. To explore greener possibilities as well as to get some insights into the role of the different graphenic supports (GO, rGO, carbon black, and graphite nanoplatelets), we prepared, under the same standard conditions, a variety of heterogeneous Cu catalysts and systematically evaluated their composition and catalytic activity in azide–alkyne cycloadditions as a model reaction. The use of sustainable graphite nanoplatelets (GNPs) afforded a stable Cu I catalyst with good recyclability properties, which are compatible with flow conditions, and able to catalyze other reactions such as the regio‐ and stereoselective sulfonylation of alkynes (addition reaction) and the Meerwein arylation (single electron transfer process). Abstract : Which graphene derivative? Efficient, green, and recyclable heterogeneous graphene‐based Cu catalysts, with different types of graphene derivative, have been applied in batch and continuous‐flow click reactions, sulfonylations, and Meerwein arylation.